2008
DOI: 10.1103/physrevb.78.054417
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a periodic magnetic field and spin-polarized current on the magnetic dynamics of a monodomain ferromagnet

Abstract: Motivated by numerous experiments on the magnetization reversal by electric current and magnetic-field pulses, we performed a numerical simulation within a macrospin model with periodic field and spin-polarized current, also taking into account the anisotropy of damping. It is shown that the magnetic dynamics is strongly affected by the variation of frequency and shape of the pulses. In particular, single rectangular pulses of the current can be used to achieve faster magnetization reversal, whereas harmonic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 53 publications
0
18
1
Order By: Relevance
“…Different from the precession without magnetic field, the temporal evolution of the magnetization component M x /M s has a "sag" in the oscillation crest at a perpendicular magnetic field. Although this phenomenon had also been reported by Siracusano et al [48] and Horley et al [49,50], the explanation is not found. We shall give a systematic explanation of this phenomenon later.…”
Section: Resultscontrasting
confidence: 42%
“…Different from the precession without magnetic field, the temporal evolution of the magnetization component M x /M s has a "sag" in the oscillation crest at a perpendicular magnetic field. Although this phenomenon had also been reported by Siracusano et al [48] and Horley et al [49,50], the explanation is not found. We shall give a systematic explanation of this phenomenon later.…”
Section: Resultscontrasting
confidence: 42%
“…This approach simplifies the visualization of the phase portraits, offering a useful "recipe" for obtaining a clear 2D plot of a 3D magnetization curve. The superimposed plots may become complicated for phase portraits composed of numerous loops, but this situation does not occur in a system subjected to constant fields and currents (Horley et al, 2008). To improve the calculation performance for the LLG equation written in the stereographic projection, it is important to optimize the procedure for projector pole switching.…”
Section: Stereographic Projectionmentioning
confidence: 99%
“…Thus, despite magnetization vector deviates from the film plane for certain periods, the average over the whole oscillation cycle will remain parallel to the axis Z, so that this type of phase portrait is called in-plane precession (IPP). The dynamic diagram shows how efficient is the use of the Hausdorff dimension for visual separation of the parameter areas where in-plane and out-of-plane precession takes place; it also works fine for complicated cases of multi-loop phase portraits triggered by pulsed fields and currents (see Horley et al, 2008). Now, having the idea of what to expect from the solution of the LLG equation, let us discuss in detail its different representations (including strengths and weaknesses thereof from the computational point of view), as well as numerical methods required for the most efficient and accurate solution of this equation.…”
Section: Landau-lifshitz-gilbert Equationmentioning
confidence: 99%
“…Among them we find steady-state in-plane and out-of-plane oscillations of the magnetization, switching between antiparallel (AP) and parallel (P) configurations, static canted states, or even chaotic motion. 9,10 In symmetric MTJs with very thin tunneling barriers of typically MgO, in which both magnetic layers consist of the same material, e.g., in-plane magnetized CoFeB, largeamplitude out-of-plane oscillations can be induced without an external magnetic field. 11 However, thicker MTJs with interfacial perpendicular anisotropy may exhibit largeamplitude oscillations as well.…”
Section: Introductionmentioning
confidence: 99%